The sustainable harvesting of non-timber forest products from natural forests in the southern Cape, South Africa : development of harvest systems and management prescriptions - Vermeulen, Wessel Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2009.